3D graphene-cellulose nanofiber hybrid scaffolds for cortical reconstruction in brain injuries. (5th September 2019) - Hwang, Do Won; Park, Jong Bo; Sung, Dongchul; Park, Subeom; Min, Kyung-Ah; Kim, Kyu Wan; Choi, Yoori; Kim, Han Young; Lee, Eunji; Kim, Han Soo; Jin, Mo Ses; Park, Minsung; et al.
Abstract: Designing the nature-driven 3D scaffold is essential for reconstructing of the injured brain in association with stem cell replacement therapy. In this paper, we developed brain cortex-mimetic 3D hybrid scaffolds and applied them to a motor-cortectomy rat model. Graphene oxide bacterial cellulose (GO-BC) hybrid scaffold integrated GOs stably and homogeneously within BC nanofibrous building blocks made of BC and amphiphilic comb-like polymers (APCLP). Density functional theory calculations and molecular dynamics simulations revealed higher binding energies between GO-BC and APCLP than between GO or APLCP with BC. The monodispersed human neural stem cells (F3 cells) incorporated within the GO-BC scaffold generated a large number of differentiated neurons with robust neurite outgrowths and possible synapse formation in vitro . In corticectomized rats and nude mice, highly sensitive photoacoustic signals visualized the GO-BC at the implant site. Moreover, the implanted F3 cells within GO-BC were found to survive/proliferate and differentiate to neuronal lineage from the showing neuronal and synapse markers shown on ex vivo immunofluorescence staining in bioluminescence imaging. Cortex-mimetic and stem cell-instructive monodisperse GO-BC hybrid scaffolds are likely to be appropriate nanoplatforms for stem cell implantation to reconstruct injured/lost brain tissues and actively differentiate neural stem cells.